Halal Logistics in Focus: A Bibliometric Analysis and Strategic Review of Indonesia’s Global Competitiveness - Fittriya, Nurul Laili; Darno, Darno (Jurnal Logistik Indonesia, 2024)
As the country with the largest Muslim population in the world, Indonesia holds significant potential in developing halal products, particularly in the food and beverage sector. Although 2024 saw a substantial increase in the number of companies applying for halal product testing, this growth was not accompanied by a rise in halal product export volumes. Data indicates that Indonesia’s halal product exports experienced a decline of approximately 2.1% in 2024, decreasing from USD 42.32 billion to USD 41.42 billion compared to the previous year. This downward trend presents a strategic challenge in strengthening Indonesia's competitiveness in the global halal market, especially amid growing demand from both Muslim and non-Muslim countries. One critical area requiring attention is halal logistics, which continues to face various obstacles, including limited international halal certification, ambiguous guidelines, weak financial and institutional coordination, low market demand, and the absence of standardized cost-effectiveness measures. This study aims to map the research trends on halal logistics published in reputable journals focused on Islamic economics. A total of **175 Scopus-indexed scientific publications** were analyzed using the VOSviewer software to generate a bibliometric map of the field’s development. The findings show that “halal logistics is a central focus in global literature; however, Indonesia’s research contribution remains relatively limited. Therefore, strengthening local research capacity is essential to enhance Indonesia’s strategic role in the international halal logistics ecosystem.